Time Spent Using Digital Technology, Loneliness, and Well-Being Among Three Cohorts of Adolescent Girls and Boys – A Moderated Mediation Analysis - Boris Jokić; Zrinka Ristić Dedić; Jana Šimon (Psychological Topics, 2024)
Significant changes to daily life and educational routines due to the COVID-19 pandemic resulted in changes in social interactions and might have contributed to an increase in screen-based activities, loneliness, and mental health issues among adolescents. Two years after the pandemic outbreak, the present study examined the relationships between time spent using digital technology (DT), loneliness and well-being among three cohorts of adolescents in Croatia. A moderated mediation model of relationship between time spent using DT and well-being was tested, with loneliness as a potential mediator and gender as a moderator. A nationally representative sample included 3706 11-year-olds, 3866 13-year-olds and 8815 17-year-olds. The study was conducted in lower and upper secondary schools in the spring of 2022. The questionnaire contained a single item self-report measure of time spent using DT and loneliness, while the adapted WHO-5 was used for measuring adolescents’ well-being. Results indicated that time spent using DT was positively associated with loneliness and negatively associated with well-being. Loneliness mediated the relationship between time spent using DT and well-being in all cohorts. This mediation was moderated by gender in the group of 11-year-olds only. Gender moderated the direct effect on well-being among 11- and 13-year-olds. Effects were stronger among girls and younger participants. The results are discussed in light of the displacement hypothesis, which posits that negative effects on well-being are a consequence of the replacement of in-person activities with screen-based activities.